Molecular insights into adulteration dynamics in clarified butterfat: an image based approach - Awasthi, Avinash Kaushal; Gupta, Pallavi; Noor, I. M. (John Wiley and Sons, 2025)
Clarified butterfat, commonly known as desi ghee, is one of the most important edible products of the dairy industry. There are many types of materials used to adulterate the clarified butterfat. This study presents the development of a protocol for the image acquisition of various controlled pure and adulterated samples of clarified butterfat. Further, its analysis is proposed using image processing tools for developing a model to identify the various adulteration levels in clarified butterfat (cow ghee) that is adulterated with vegetable fat. The processed images are analysed for pixel intensity, crystalline structures, yellowness, and skeleton factors to evaluate the purity of butterfat (ghee) and matched with impure samples of 10%, 20%, 30%, 40%, and 50% adulteration levels using discriminant analysis. The study delves into the effects of varying adulteration levels on the molecular characteristics of clarified butterfat, considering both intrinsic and extrinsic factors. Changes in crystalline values are accompanied by increasing levels of adulteration, attributed to shifts in triglyceride composition induced by the addition of hydrogenated vegetable fat. The selected parameters can be used as a substitute method at a standard temperature of 28–32 °C with benefits of ease, speed, accuracy, larger sample size for repeatability with an extent up to 90% of precision by critically following the developed protocol.